Contemporary corporate governance issues in Australian banking environment - Htay, Sheila Nu Nu; Syed, Ahmed Salman (Choice College of Arts & Commerce, Pune., 2013)

(untitled)
Corporate governance issues become getting attention from the regulators, industrial players and investors due to the financial crises and recent corporate failures. Australia is ranked in the fourth position in terms of having good corporate governance practices after United Kingdom, United States of America and Canada. In Asia, Australia is one of the leading countries which are having good corporate governance codes and practices. However, it does not mean that it has the perfect governance system and thus, the objective of this study is to examine the contemporary corporate governance issues and problems in Australian Banking sector. This paper is written based on the critical review of the literature. This paper raises the corporate governance issues in Australian banking sector related to the regulatory environment, competitive nature of banking industry, profit maximization driven mood, agency conflicts, behavior and culture. It is expected that the issues raised in this paper will open the eyes of the Australian regulators, bankers and researchers for the betterment of corporate governance practices in the future.